Humor at work: a study about the relationship between humor styles, satisfaction with management and individual job performance - Souza, Ariana Marchezi de; Araujo, Bruno Felix von Borell de; Andrade, Allana Matos de; Cerqueira, Alexandre dos Santos (Revista de Administração da UFSM, 2019)
This research investigated the relation among the humor styles, the employees satisfaction with their leader, and job performance of employees, through a quantitative study. In order to measure the constructs, two questionnaires, validated in previous studies, were used: The Humor Styles Questionnaire from Martin et al. (2003) and the Job Satisfaction Scale from Siqueira (1995). The score for individual performance was obtained from an instrument of assessment called “assessment 360º” used by the company studied. 234 valid answers were obtained and the relation among the variables was studied through the Structural Equation Modeling Method, with PLS estimation (Partial Least Squares – Path Modeling). Were identified significant positive relations among the positive styles of humor (affiliative and self-enhancing) and the employees satisfaction with their leader, and between satisfaction with their leader and job performance. On the other side, significant negative relations were verified among negative styles (aggressive and self-defeating) and employees satisfaction with their leader, been an aggressive humor responsible for 16,81% of dissatisfaction with their leader. This results suggest that organizations may benefit from the selection of leaders with the proper humor styles to reach specific behavior and organizational results.